Mrs. Dalloway e a reescritura de Virginia Woolf na literatura e no cinema - Silva, Carlos Augusto Viana da (2007)
This dissertion investigates the rewrinting of Virginia Woolf's literary universe to literature and to film, through the analusis of the rewritings of the novel Mrs. Dalloway (1925): the film Mrs. Dalloway (1998), directed by Marleen Gorris, the novel the hours (1998), by Michael Cunningham, and the film The hours (2002), directed by Stephen Daldry. Our hypothesis is that the rewriting narratives are more tradicional, i.e. they have a new lineae arrangement and do not follow an avant-garde tendency due, mainly, to their translators- style. In order to confirm such hypothesis, we have analyzed some translation strategies, used in the creation of Woolf's imagery to new audiences. In each narrative, general questions on plot and on the construction of time and space have been taken into account. The strategies obser ed in the film Mrs. Dalloway were the following: linearity (narrative organization), flashback, voice-over, and montage; in the film The hours, the fllowing strategies have been investigated: delineation of plot (the cration of three parallel stories), continuity of image elements (montage), silence and actors/actress's expressions, and multiple perspectives. The analysis led us to conclude that these narratives have theeir own format (with a particular linear arrangement) ando do not follow the avant-garde tendency of Woolf's novel due not only to the questions inherent in the conematographic medium (the increase of the audience, the creation of linear narratives, influenced by the classic Hollywoodian narratives, etc), but also to the translators' style and conception of cration. The anlysis is basec on lefevere1s idea of reweiting as a soft of translation (1992); on the conception of translation in Toury's Descriptive Studies (1995), on Even-Zohar's polysystem theory; and on some studies that deal with the relationship between literature and cinema such as Bordwell (1985), Vanoye & Gollliot-Lété (1994), Aumont et al (1995) and Cruz (1997).